2022
DOI: 10.1002/1878-0261.13286
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics roadmap for therapy selection in cancer genomics

Abstract: Bioinformatics roadmap for cancer therapy selection M. J. Jim enez-Santos et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 340 publications
0
5
0
Order By: Relevance
“…In the early stages of research, statistical approaches were employed, as demonstrated by Anderson et al [23] in their meta-analysis of long-term weight loss trends. A further breakthrough was made by Jiménez-Santos et al in federated learning for secure medical data sharing [24]. The inclusion of genetic and non-genetic attributes has enriched predictive models.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages of research, statistical approaches were employed, as demonstrated by Anderson et al [23] in their meta-analysis of long-term weight loss trends. A further breakthrough was made by Jiménez-Santos et al in federated learning for secure medical data sharing [24]. The inclusion of genetic and non-genetic attributes has enriched predictive models.…”
Section: Related Workmentioning
confidence: 99%
“…A further breakthrough was made by Jiménez-Santos et al. in federated learning for secure medical data sharing [ 24 ]. The inclusion of genetic and non-genetic attributes has enriched predictive models.…”
Section: Related Workmentioning
confidence: 99%
“…Novel Precision Medicine therapies, such as BRAF V600E inhibitors in patients with melanoma and PD1/PD-L1 immunotherapy for melanoma, lung, kidney, and other types of cancer [ 109 , 110 ], are enabling more efficient treatment with minimized side effects. In the following years, with the evolution of translational bioinformatics, advances in data sharing and integration are expected [ 111 ], improving collaborative and multidisciplinary teams [ 112 ], advances in data mining [ 113 ], expanding the ability to generate and analyze data [ 114 ], and planning therapies through better diagnosis [ 115 ] with the identification of new biomarkers and drug targets [ 116 , 117 ].…”
Section: Computational Perspectivesmentioning
confidence: 99%
“…Cancer is a group of genetic diseases that has been classically approached with a one-size-fits-all strategy, which often resulted in treatment inefficacy and adverse drug reactions [1], underlining the existence of intertumour heterogeneity [2]. Personalised precision oncology is a novel therapeutic strategy that aims to provide tailored treatments to cancer patients according to the molecular characteristics of individual tumours [3,4]. Breast cancer research has contributed to the foundations of personalised precision oncology by identifying biomarkers to guide patient stratification and selection of targeted therapies.…”
Section: Introductionmentioning
confidence: 99%